Von illusionärer Wirklichkeit und wahrer Illusion Zu Carlo Gozzis "Fiabe teatrali" - Winter, Susanne (Vittorio Klostermann GmbH, 2007)
In the eighteenth century, Venice was not only a centre of theatre life but also a centre for discussion about theatre. In literary and theatre history the well-known Venetian theatrical dispute, with its protagonists Carlo Goldoni and Carlo Gozzi, seem to provoke a simplistic reproduction of the polemics. A predominantly negative image of Gozzi is correlated with an appreciation of Goldoni and his dramaturgical reform, whrereas while Gozzi is considered the savior of the commedia dell´arte, Goldoni appears as ist grave-digger. This study tries to break open such prejudice, reading Gozzi´s "Fiabe teatrali" as a veritable counterpoint to Goldoni´s comedies and Enlightenment drama. Against the background of Italian theatre in the 18th century and contemporary Venetian theatricality, Gozzi´s intention, as well as the speical caracteristics of his tales for the theatre, becomes evident. Using fairy tales and commedia dell´arte as basic constituents for his "Fiabe teatrali", Gozzi responds to a theatre that emphasizes the reflection of everyday life and follows the concept of utility. The combination of elements are distanced from reality in a way that resembles an ars combinatoria, based on a structure of constrasts that underlines its artificial character. This displays the autonomy of theatrical reality and and the importance of imagination. However, the fairy tale illusion refers back to reality in two ways: on the one hand the traditional masks comment directly current events, on the other hand theatrical illusion indirectly reveals truth that remains secret in discourse. As a new dramatic genre the "Fiabe teatrali" open the possibility to reflect on the constructed character of reality and to set on stage the problematic nature of the perception of truth.